2015
DOI: 10.1002/jso.23860
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel radiation‐induced sarcoma cell line

Abstract: Background Radiation-induced sarcoma (RIS) is a potential complication of cancer treatment. No widely available cell line models exist to facilitate studies of RIS. Methods We derived a spontaneously immortalized primary human cell line, UACC-SARC1, from a RIS. Results Short tandem repeat (STR) profiling of UACC-SARC1 was virtually identical to its parental tumor. Immunohistochemistry (IHC) analysis of the tumor and immunocytochemistry (ICC) analysis of UACC-SARC1 revealed shared expression of vimentin, os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Elucidating risk factors for the development of RIS has historically been difficult given its rare occurrence. Also, RIS tumors are aneuploid and have complex genomics making it a challenging disease to understand [ 15 ]. Our group has previously evaluated evidence-based practices for RIS and found no prospective, randomized trials on RIS of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating risk factors for the development of RIS has historically been difficult given its rare occurrence. Also, RIS tumors are aneuploid and have complex genomics making it a challenging disease to understand [ 15 ]. Our group has previously evaluated evidence-based practices for RIS and found no prospective, randomized trials on RIS of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Although some organ systems such as thyroid, breast and bone marrow are more radiosensitive, the mechanism of radiation associated sarcoma development remains relatively unclear . Mechanisms postulated include loss of heterozygosity in irradiated cell nuclei leading to tumor suppressor gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Disease specific survival is impacted by several factors which vary slightly among cohorts: histologic sub‐type and grade, disease stage, tumor location and presence of necrosis The addition of chemotherapy during primary tumor treatment may have a synergistic effect with radiation to increase risk and decrease latency time to subsequent sarcoma . Although the underlying explanation is controversial, studies have suggested that radiation associated sarcomas have a worse prognosis when compared to their spontaneously occurring counterparts .…”
Section: Introductionmentioning
confidence: 99%